Cultura turística de los empresarios del sector turismo del distrito de Salaverry. - Ortiz Gutiérrez, José Luis (2018)
The purpose of this document is to identify expressions of tourism culture of entrepreneurs in the tourism sector in the district of Salaverry, such as knowledge and management of business management with a focus on production, tourism heritage oriented to classic attractions; and the not very innovative attitude in the implementation of policies and procedures that guarantee tourist satisfaction. Affirming that the orientation of the tourist companies of Salaverry is clearly directed towards production and neglecting customer service. Another important point is the attitude of entrepreneurs facing the consideration and application of policies and procedures that guide their businesses, and the relationship with the dimensions of the tourist culture such as friendliness, tourist orientation, tourist safety and honesty. The report is structured on the basis of three chapters, aimed at the description and identification of the data obtained from the registration of tourism companies, entrepreneurs interviewed about their knowledge and attitudes, and by the collaborators vital elements applied in the company. To achieve this end, the scientific methods were used: Analytical-Synthetic and Ethnographic methods; each one of them with their respective techniques and instruments, the same that were used for the collection, processing, systematization and analysis of the data generated in the present investigation.